ESG PERFORMANCE, DEBT EQUITY CHOICES, AND RAPID ADJUSTMENTS IN INDONESIA - Pujiastuti, Arum; Yunita, Rizki Dini Shandra; Astuti, Fitria Yuni (UI Scholars Hub, 2024)
Previous research has explored the relationship between sustainability performance and firm performance; however, there is a noticeable scarcity of studies addressing the intricate connection between sustainability performance and firm financing. This study aims to bridge this gap by investigating how sustainability performance impacts firm financing decisions and capital structure adjustment in the context of Indonesia. Leveraging Environmental, Social, and Governance (ESG) performance data specific to Indonesia, this research contributes novelty to financing choices and the speed at which firms adjust their leverage. Through a combination of fixed-effect modelling and dynamic panel Generalized Method of Moments (GMM), the study employs a dataset containing 506 firm-year observations, evenly distributed between ESG firms and non-ESG firms. The findings demonstrate that firms that incorporate ESG principles into their operations display a greater inclination towards equity financing. Additionally, the research underscores that ESG firms exhibit a more rapid adjustment pace toward their target leverage ratios compared to non-ESG firms.